ISLAMIC EDUCATION IN SRI RATU TAJUL SAFIATUDDIN’S PERIOD (HISTORICAL REVIEW) - Putra, Rahmad Syah (UIN Ar-Raniry, 2015)
The background of this study is to see how the Islamic education in Ã‚Â Sri Ratu Tajul Alam SafiatuddinÃ¢â‚¬â„¢s period, at that time the kingdom of Aceh Darussalam peak of its glory (Century XVII), it was visited by many scholars (Ulama and the Poet), foreign and domestic. Among those who came, there are some scholars who stayed in Aceh and return to his homeland as well. While in Aceh, they became a teacher, especially in the science of religion and the author of books on various branches of science. Since the number of teachers and authors who live in Aceh make Aceh as